Syntheses, structures and luminescence properties of five coordination polymers based on designed 2, 7-bis(4-benzoic acid)-N-(4-benzoic acid) carbazole. Issue 19 (28th April 2017) - Chen, Dong-Hui; Lin, Ling; Sheng, Tian-Lu; Wen, Yue-Hong; Hu, Sheng-Min; Fu, Rui-Biao; Zhuo, Chao; Li, Hao-Ran; Wu, Xin-Tao
Abstract : Five coordination polymers based on a novel carbazole-based ligand show a linear correlation to Ni 2+ and Eu 3+ concentration. Abstract : Herein we report five porous luminescent coordination polymers (CPs), namely, [Zn3 (L 27 )2 (DMA)6 (H2 O)4 ] n (TCZ-001 ), [Zn3 (L 27 )2 (DMA)6 (CH3 CH2 OH)2 ] n (TCZ-002 ), [Zn3 (L 27 )2 (DMA)6 (CH3 OH)] n (TCZ-003 ), [Cd3 (L 27 )2 (DMA)6 (H2 O)2 ] n (TCZ-004 ), and [Cd9 (L 27 )6 DMA13 (4, 4′-BPY)2 (OH)2 (H2 O)13.5 ] n (TCZ-005 ) [H 3 L 27 = 2, 7-bis(4-benzoic acid)- N -(4-benzoic acid) carbazole, DMA = N, N -dimethylacetamide, 4, 4′-BPY = 4, 4′-bipyridine, TCZ = "T"-shape carbazole-based polymers, L 27 = fully deprotonatedH 3 L 27 3− ligand]. All of the five CPs were assembled from a novel luminescent carbazole-based ligand. X-ray crystallography showed thatTCZ-001 is a 3-connected one-dimensional (1D) chain structure with a {4 2 ·6} topology.TCZ-002 possesses a 3, 6-connected three-dimensional (3D) framework with a point symbol of {4 2 ·6}2 {4 4 ·6 2 ·8 7 ·10 2 }.TCZ-003 displays a 3, 6-connected two-dimensional 2D network with a Schläfli symbol of {4 11 ·6 4 }·{4 3 }2, which is a new topology.TCZ-004 features a 3, 6-connected 2D net with a {4 3 }2 ·{4 6 ·6 6 ·8 3 } topology. InTCZ-005, the structure can be classified into two groups: one of the two groups is a 3-connected 1D chain structure with a {4 2 ·6} topology, similar toTCZ-001 ; the other one possesses a 3, 3, 3, 4-connected network with a Schläfli symbol of {4 2 ·6 3 ·8}{4 2 ·6}3 . The structure ofTCZ-005 could be described as an SP 1-periodic net (4, 4)(0, 2) in the 1D_2D.ttd database.TCZ-001, TCZ-003 andTCZ-004 show a remarkable response to the Ni 2+ concentration in DMA, H2 O or EtOH. Some of Zn 2+ ions were replaced by Ni 2+ ions and the rate of the transmetalation depended on the concentration of Ni 2+ ions. Also, changing part of the metal node would transform the colour of emitted light. Additionally, the colour of the luminescence displays a linear correlation with the Ni 2+ concentration range from 0.005 to 0.35 M (mol L −1 ). Besides selective sensing of Ni 2+, TCZ-004 can also be utilized to detect Eu 3+ in DMA solution. Thus, several potential sensory probe materials for Ni 2+ and Eu 3+ detection in DMA solution have been obtained.